RODA BERPUTAR SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA DI MI IZZUL ISLAM - Noviatun Hasanah; Firdaus Ainul Yaqin; Farich Purwantoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of rotating wheel media as an alternative learning media in increasing student learning activity in Arabic language learning at MI Izzul Islam. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the use of rotating wheel media can increase student learning activity, which is characterized by increased student participation in answering questions, courage in expressing opinions, and student involvement in the learning process. In addition, this media also creates a more interesting, interactive, and enjoyable learning atmosphere. Supporting factors include student enthusiasm and teacher creativity, while inhibiting factors include limited time and media readiness. Thus, the rotating wheel media is effective in increasing student learning activity in Arabic language learning.